2017
DOI: 10.1016/j.jns.2017.07.037
|View full text |Cite
|
Sign up to set email alerts
|

Tele-neurology in sub-Saharan Africa: A systematic review of the literature

Abstract: Background The rapid advancement in telecommunications on the African continent has opened up avenues for improving medical care to underserved populations. Although the greatest burden of neurological disorders is borne by Low-and-Middle Income Countries (LMICs) including sub-Saharan Africa (SSA), there is a profound paucity of neurologists to serve the population. Telemedicine presents a promising avenue for effective mobilization and utilization of the few neurologists in Africa. Objective To systematical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 33 publications
0
57
0
Order By: Relevance
“…In fact, we have recently proposed tele-neurology and its sub-discipline such as tele-rehabilitation and mobile technology interventions for vascular risk factor control as promising avenues to improving the reach of neurology services in sub-Saharan Africa. 4446 Our findings in the present study have identified reasons for non-attendance of physiotherapy required for recovery from stroke and has collected data of relevance in preparation for tele-rehabilitation clinical trials among stroke survivors in resource-limited settings.…”
Section: Discussionmentioning
confidence: 72%
“…In fact, we have recently proposed tele-neurology and its sub-discipline such as tele-rehabilitation and mobile technology interventions for vascular risk factor control as promising avenues to improving the reach of neurology services in sub-Saharan Africa. 4446 Our findings in the present study have identified reasons for non-attendance of physiotherapy required for recovery from stroke and has collected data of relevance in preparation for tele-rehabilitation clinical trials among stroke survivors in resource-limited settings.…”
Section: Discussionmentioning
confidence: 72%
“…The SARS-CoV-2 pandemic has wrecked untold havoc in the care of prevalent health conditions such as cancer, myocardial infarction and acute stroke in HICs [ [15] , [16] , [17] ]. A potential approach may be to accelerate the adoption of teleneurology [ [18] , [19] , [20] ] and mobile health interventions [ 21 , 22 ] for CVD risk reduction in our low-and-middle income settings in the wake of an anticipated rise in the COVID-19 cases with its associated health service delivery disruptions.…”
Section: Discussionmentioning
confidence: 99%
“…The training of other team members such physiotherapists, occupational and speech therapists, and dieticians, should be promoted through local neurological and international societies such as the International Parkinson and Movement Disorder Society. A previous review suggested that tele-neurology can be deployed for training of health care workers through local, regional, and intercontinental networks (61).…”
Section: Solutions Neededmentioning
confidence: 99%